The Capitalization of the 21st Century Secular Temples and Strategic Sabotage - Bilen, Burcin Mizrak (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2019)
The concepts such as culture, technology, design, or human capital, the tangible benefits of which are vague, are mostly effective in setting the financial value of a company, a work of art, a software, or any product. This situation triggered both sectoral and academic studies intended for analyzing and measuring this vagueness. The subject of what the 'good design is, which is an important input affecting the value of the physical environment in the cities, and the problematic of its measurability started to occupy the architectural research agenda. The prevalent view that the more intangible benefits are detected and disclosed the more 'good designs the cities will have has prompted the people who conduct research in this field to develop very comprehensive models. However, these studies that started in the '90s unfortunately failed to have the expected impact on creation and development of more livable cities. In this context, to get a better insight of how the financial sector reads these benefits, the subject has been opened up for discussion within the framework of the power theory of value, by searching for traces of the differential capitalization and strategic sabotage concepts in the physical space, which are in favor of the rootless transnational capitalist class that is at the center of this theory and the modern-day secular temples owned by the 1 %of the architectural patronage who finance the highest budget projects in cities and its spatial dimension have been seen through this lens. As an outcome of the study, different values these temples and the spatial dimension concerning them carry for different actors, and how these different values or benefits are capitalized, and the types of sabotages they cause have been explained in detail, and it has been targeted to make a provocative contribution to the literature.
Keywords: Architecture of 1%; power theory of value; differential accumulation; capitalization; radical imaginary; strategic sabotage; ARCHITECTURE; LONDON; ICON